Diagnostic Accuracy of Core Needle Biopsy of Breast Lesions in Maharat Nakhon Ratchasima Hospital - Poklang, Vacharee (Maharat Nakhon Ratchasima Hospital Journal, 2024)
Objective: To determine the accuracy, sensitivity and specificity of core needle biopsy of breast lesions in Maharat Nakhon Ratchasima Hospital. Material and Methods: The files of department of pathology, Maharat Nakhon Ratchasima hospital were searched for cases of breast lesions, between 1 October 2008 to 30 September 2010. Hematoxylin-eosin stained slides from manual core needle biopsy and subsequent open surgery specimens and their surgical pathology reports were retrospectively studied. The overall accuracy, sensitivity and specificity were analyzed. Results: One hundred and seventy cases with adequate tissue samples for histopathologic evaluation were included in this study. One hundred and sixty cases (94.12%) were correctly diagnosed by core needle biopsy compared with subsequent open surgery, In 114 cases, Invasive carcinomas were correctly diagnosed by core needle biopsy which mostly were invasive ductal carcinoma. Benign lesions were correctly proved in 46 cases which mostly were fibroadenoma. The accuracy of core needle biopsy in diagnosis of breast lesions was 94.11%. Conclusion: In this study, core needle biopsy yieldeds an accuracy rate of 94.11%. The sensitivity and specificity are 91.93% and 100% respectively. This is in line with several researches which report core needle biopsy as an excellent technique for palpable breast lesion creating high level of accuracy rate, sensitivity and specificity in performing a histological diagnosis of breast lesions.